2015
DOI: 10.1371/journal.pone.0118344
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electronic Cigarette Emissions on Systemic Cotinine Levels, Weight and Postnatal Lung Growth in Neonatal Mice

Abstract: Background/ObjectiveElectronic cigarette (E-cigarettes) emissions present a potentially new hazard to neonates through inhalation, dermal and oral contact. Exposure to nicotine containing E-cigarettes may cause significant systemic absorption in neonates due to the potential for multi-route exposure. Systemic absorption of nicotine and constituents of E-cigarette emissions may adversely impact weight and lung development in the neonate. To address these questions we exposed neonatal mice to E-cigarette emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 31 publications
14
95
1
1
Order By: Relevance
“…Our results revealed that there were significant levels of cotinine in the mice exposed to e‐cigarettes, whereas it was not detectable in the clean air control mice. Importantly, the measured mean plasma levels (ie, average of 53.97±3.61 ng/mL; Figure 1) were in fact comparable to those observed in humans and other animal e‐cigarette exposure models, that is, 30 to 250 ng/mL 46, 47, 48…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Our results revealed that there were significant levels of cotinine in the mice exposed to e‐cigarettes, whereas it was not detectable in the clean air control mice. Importantly, the measured mean plasma levels (ie, average of 53.97±3.61 ng/mL; Figure 1) were in fact comparable to those observed in humans and other animal e‐cigarette exposure models, that is, 30 to 250 ng/mL 46, 47, 48…”
Section: Resultssupporting
confidence: 75%
“…Thus, key markers to be noted of this system are (1) the cotinine levels found in the plasma of our e‐cigarette–exposed mice (average of 53.97 ng/mL) overlaps with those observed in established human and animal e‐cigarette exposure models46, 47, 48 but undetectable in clean air samples, (2) which were obtained/observed using a device and an e‐liquid mixture that are widely used by humans34, 35, 36, 73 and (3) under real‐life puffing topography experimental conditions. 24–33 …”
Section: Discussionsupporting
confidence: 54%
“…39 The mice exposed to the ENDS solution containing nicotine had decreased weight gain and impaired postnatal lung growth compared with mice exposed to room air. ENDS solutions have also been shown to be cytotoxic to human embryonic stem cells.…”
Section: Ends Secondhand and Thirdhand Aerosolmentioning
confidence: 97%
“…In vivo studies in mice show E‐cigarette exposure stunts growth (McGrath‐Morrow et al. 2015) although this may be limited to nicotine‐containing E‐cigarettes (Larcombe et al. 2017).…”
Section: Introductionmentioning
confidence: 99%